PARAMETER ESTIMATION OF STEADY OPERATIONAL MODES OF GAS SUPPLY SYSTEMS - Грудз, Володимир Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Methods of construction of integral influence factors for gas pipeline transportation system in order to estimate its parameters at steady operational modes are presented. It is shown an example of application of proposed methods for main gas pipeline “Soyuz”.